38 Prognostic validation of partition values obtained with conventional two-dimensional and doppler echocardiography to grade tricuspid regurgitation severity. (17th January 2020) - Previtero, M; Guta, A C; Ochoa-Jimenez, R C; Figliozzi, S; Palermo, C; Baritussio, A; Cecchetto, A; Aruta, P; Iliceto, S; Badano, L P; Muraru, D
Abstract: Background: Morbidity and mortality associated with severe tricuspid regurgitation (TR) have prompted interest in new corrective transcatheter procedures. However, to properly select patients for interventional procedures, and to assess their effectiveness, a reliable and reproducible grading system of TR severity is mandatory. However, the cut-off values used by current guidelines to differentiate among mild, moderate and severe TR lack clinical validation. Purpose: We aimed to obtain the threshold values of the currently recommended quantitative echocardiographic parameters used to grade TR severity using pts' outcome as a reference. Methods: 296 pts, with at least mild TR and complete 2D, 3D and Doppler echocardiographic study, were enrolled and assessed for potential confounders: age, NYHA class, left ventricular ejection fraction, coexistent valvular heart disease and right ventricular (RV) systolic pressure. Average diameter of the vena contracta (VCavg), effective regurgitant orifice area (EROA), regurgitant volume (RVol) and regurgitant fraction (RF) were obtained to grade TR severity. Median follow-up was 47 (17-80) months. The primary composite endpoint was the occurrence of death of any cause or hospitalization for right heart failure (RHF). Survival curves for the composite endpoint were divided in quartiles at median follow-up. Cut-off values for the echo parameters were derived to grade mild (below the 1st quartile), moderate (between 1st and 3rd quartiles), and severe (above the 3r quartile) TR. Results: 33 deaths and 72 hospitalizations for RHF occurred. Event-free rate from death or RHF at the end of follow-up was 14%, 46% and 93% in pts with severe, moderate, and mild TR, respectively. Differences reached statistical significance early (at 1 month), and lasted during the whole follow-up period (Figure). The new threshold values for mild, moderate and severe TR are summarized in Table. Conclusions: Partition values of quantitative echo-Doppler parameters used to grade mild, moderate and severe TR according to pts' clinical outcome are significantly lower than those currently reported in guidelines. Further studies are needed to test if these new threshold values for severe TR will translate in earlier referral of pts to valve repair and improved prognosis.